Changing trends in barriers to cataract surgery in India. - Vaidyanathan, K. (World Health Organization, 1999)
Cataract is a major cause of blindness in Asia. Efforts in India to provide cataract surgical services have had limited success in reaching the cataract-blind population. Earlier studies identified the major barriers to cataract surgery as poverty, lack of transportation or felt need, or sex related; and the critical barriers in rural areas as lack of awareness, difficult access, and cost. Compared with these earlier data, the results of the present study in Karnataka State indicate a shift in the character of the barriers. They now appear to be more related to case selection and service provision. These shifts are analysed and alternative strategies to increase the uptake to cataract surgery are recommended.